The influence of the occupational status on German bank employees’ level of job satisfaction - Breuer, Nele Frauke (2018)
This research aims to examine the impact of German bank employees’ occupational status on their level of job satisfaction. The study further investigates how job characteristics of different occupational groups influence the participants’ level of job satisfaction and which job characteristics the bank needs to improve to increase their employees’ overall job satisfaction. Twelve bank employees were interviewed for the purpose of this research and the findings were analyzed using content analysis. Emerging themes were explored and discussed accordingly. The findings obtained through this research indicate that the occupational status of German bank employees does not directly influence their level of job satisfaction. While employees of the same occupational group have same or similar tasks, the perception of whether a sufficient amount of job characteristics is present in their jobs depends on each individual’s own perception. Nevertheless, the findings of this study did confirm a positive relationship between job characteristics and job satisfaction. Participants that perceived their jobs to entail sufficient amounts of the investigated job characteristics were more satisfied with their jobs than participants that did not perceive job characteristics do be sufficiently present in their jobs. The study further identified that the investigated bank needs to improve the manner in which feedback is given, as well as the content that is covered during feedback meetings, to improve the overall job satisfaction of their employees.